Synthesis and application of magnetite dextran-spermine nanoparticles in breast cancer hyperthermia - Avazzadeh, Reza (Prog Biomater, 2017)
Cancer treatment has been very challenging in recent decades. One of the most promising cancer treatment methods is hyperthermia, which increases the tumor temperature (41–45 °C). Magnetic nanoparticles have been widely used for selective targeting of cancer cells. In the present study, magnetic dextran-spermine nanoparticles, conjugated with Anti-HER2 antibody to target breast cancer cells were developed. The magnetic dextran-spermine nanoparticles (DMNPs) were prepared by ionic gelation, followed by conjugation of antibody to them using EDC-NHS method. Then the Prussian blue method was used to estimate the targeting ability and cellular uptake. Cytotoxicity assay by MTT showed that antibody-conjugated MNPs (ADMNPs) have no toxic effect on SKBR3 and human fibroblast cells. Finally, the hyperthermia was applied to show that synthesized ADMNPs, could increase the cancer cells temperature up to 45 °C and kill most of them without affecting normal cells. These observations proved that Anti-HER2 conjugated magnetic dextran-spermine nanoparticles can target and destroy cancer cells and are potentially suitable for cancer treatment.